Glucose and lipid effects of the ileal apical sodium‐dependent bile acid transporter inhibitor GSK2330672: double‐blind randomized trials with type 2 diabetes subjects taking metformin. Issue 7 (21st April 2016) - Nunez, D. J.; Yao, X.; Lin, J.; Walker, A.; Zuo, P.; Webster, L.; Krug‐Gourley, S.; Zamek‐Gliszczynski, M. J.; Gillmor, D. S.; Johnson, S. L.
Abstract : Aims: To investigate the pharmacodynamics, pharmacokinetics and safety/tolerability of blocking reuptake of bile acids using the inhibitor GSK2330672 (GSK672) in patients with type 2 diabetes (T2D). Methods: Subjects with T2D taking metformin were enrolled in two studies in which they took metformin 850 mg twice daily for 2 weeks prior to and during the randomized treatment periods. In the first crossover study (n = 15), subjects received GSK672 45 mg, escalating to 90 mg, twice daily, or placebo for 7 days. The second parallel‐group study (n = 75) investigated GSK672 10–90 mg twice daily, placebo or sitagliptin for 14 days. Results: In both studies, GSK672 reduced circulating bile acids and increased serum 7‐α‐hydroxy‐4‐cholesten‐3‐one (C4), an intermediate in the hepatic synthesis of bile acids. Compared with placebo, in the parallel‐group study 90 mg GSK672 twice daily reduced fasting plasma glucose [FPG; −1.21 mmol/l; 95% confidence interval (CI) −2.14, −0.28] and weighted‐mean glucose area under the curve (AUC)0–24 h (−1.33 mmol/l; 95% CI −2.30, −0.36), as well as fasting and weighted‐mean insulin AUC0 –24 h . GSK672 also reduced cholesterol (LDL, non‐HDL and total cholesterol) and apolipoprotein B concentrations; the maximum LDL cholesterol reduction was ∼40%. There was no change in HDL cholesterol but there was a trend towards increased fasting triglyceride levels in the GSK672 groups compared with placebo. In both studies, the most common adverse events associated with GSK672 were gastrointestinal, mostly diarrhoea (22–100%), which appeared to be independent of dose. Conclusions: In subjects with T2D on metformin, GSK672 improved glucose and lipids, but there was a high incidence of gastrointestinal adverse events.